The Workers Music Association singers present "L'Internationale"
Drawing of mob in the Paris Commune Poster advertising presentation by singers from the Workers Music Association of the 'L'Internationale' at the Marx Memorial House. 'In aid of an oil boat for Cuba' PO-1605